Perancangan Penilaian Kinerja Staf Logistik Perusahaan Ritel Dengan Metode Behaviorally Anchor Rating Scale (BARS) - Tanisri, Roberta Heni Anggit; Apriyani, Apriyani; Aji, Sonny Nugroho; Nadia, Ainun (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2024)
The retail company managed by the DKI Jakarta provincial government located on Tidung Island strives to improve the performance assessment of logistics staff. The performance assessment of logistics staff has so far followed the system of the company which only raises the criteria for employee assessment in general. The lack of a specific assessment system results in difficulties for management in measuring the performance of logistics staff objectively based on their duties and job responsibilities. This research aims to develop an objective employee performance assessment system using the Behaviorally Anchor Rating Scale (BARS) method. This method focuses on the preparation of assessment criteria with anchors that are repared by observing the actual activities of the work carried out by the logistics staff. The use of the BARS method in designing a performance assessment system for logistics staff on Tidung Island is very relevant because it can integrate specific behavioral approaches with geographical challenges. The result of this research is the design of a logistics staff performance assessment system in the form of an annual performance assessment form and is able to provide an objective assessment of the performance of logistics staff.